Risk factors for non communicable diseases in a metropolitan area in South of Brazil: prevalence and simultaneity - Duncan, Bruce B.; Schmidt, Maria I.; Polanczyk, Carísi A.; Homrich, Clécio S.; Rosa, Roger S.; Achutti, Aloyzio C. (Revista de Saúde Pública, 1993)
Three-quarters of deaths in Rio Grande do Sul State, Brazil, are due to non-communicable diseases - cardiovascular diseases, alone, being responsible for 35% of them. To evaluate the prevalence of risk factors for these diseases, a household survey of 1,157 randomly sampled individuals between 15 and 64 years of age was undertaken in 1986 and 1987 in census tracts of 4 areas of the city of Porto Alegre. The age-and sex-adjusted prevalence of smoking was 40%, hypertension 14%, obesity 18%, overall sedentary lifestyle 47%, and excessive alcohol consumption 7%. Thirty-nine percent of the sample presented two or more of these five risk factors, and only 22% of men and 21% of women had none of them. The high frequencies and simultaneous presence of these risk factors indicate their importance for programs aimed at the prevention of non-communicable diseases and the promotion of adult health.